PEMETAAN BAHASA DI PULAU ALOR - Editor Team (Jurnal Lazuardi, 2019)
It was realized that in the diversity of languages / dialects there were variations in languages / dialects. Language / dialect variations can occur in the language / dialect community group with a large number of speakers and a small number of community groups. Language / dialect variations can be in the form of pronunciation, vocabulary, structure, grammar. For the language / dialect community group whose number of speakers is small, such as in Alor where the speakers are not more than five hundred people, the survival of their local languages may not exceed two generations. Especially if the language variations that distinguish one speech community group from another speech community are very large, then to communicate daily using Indonesian. The chance of extinction of regional languages is even greater. Therefore, the effort to maintain, bequeath and spread is the responsibility of all parties.